Analisis Pendidikan Karakter Berbasis Nilai dalam Kurikulum Merdeka pada Pembelajaran IPS di SMP Unggulan Hamzanwadi - Nuro Sholihah; Pina Ania Putri; Liana; Ely Mazlin; Rindu Fira (Yayasan Alpatih Harapan Semesta, 2026)
Value-based character education is an essential component of the Merdeka Curriculum in fostering students’ character development. This study aims to analyze the implementation of value-based character education in social studies learning at SMP Unggulan Hamzanwadi and its influence on students’ attitudes, manners, and learning motivation. A qualitative descriptive approach was employed. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data display, and conclusion drawing, supported by triangulation to ensure validity. The findings indicate that character education is integrated through contextual learning, teacher role modeling, religious activities, and collaboration between schools and parents. Its implementation positively contributes to students’ discipline, responsibility, cooperation, and learning motivation. Therefore, value-based character education effectively supports the creation of a conducive learning environment and strengthens students’ character development.